(untitled) (The Planet, 2024)
Introduction: Acute Kidney Injury (AKI) in children is a critical medical condition with diverse etiologies, including pre-renal and renal causes. Understanding the demographic and clinical and laboratorial characteristics associated with these etiologies is crucial for timely diagnosis and management. This comparative study seeks to bridge the knowledge gap in pediatric AKI by elucidating the demographic and clinico-biochemical profiles associated with pre-renal and renal causes. Method and materials: This comparative observational study was conducted in the Department of Paediatric Nephrology, Bangladesh Shishu Hospital and Institute, Bangladesh from January 2020 to December 2021. Children aged between 1 month to 12 years of either sex, diagnosed as AKI stage 2 or 3 due to pre renal and renal causes. Results: In the pre-renal group, the majority (65.4%) of patients were infants, while in the renal group, 51.9% were from the 1-5-year age group. At baseline, oedema was significantly more in the renal group (85.2%) compared to the pre-renal group (34.6%) (p<0.001) and hypertension was exclusively observed in the renal group (77%). Conversely, hypotension was significantly more prevalent in the pre-renal group (65.4%) than in the renal group (18.5%) (p<0.001). In the pre-renal group, sodium was significantly higher than in the renal group (p<0.05). On the other hand, creatinine levels, blood urea, and potassium were significantly higher in the renal group compared to the pre-renal group (p<0.05). Conclusion: Pre-renal AKI was observed mainly in infants, whereas older children faced renal AKI and higher rates of hypotension was found in the pre-renal patients in this study.